Overview of Polyethylene Glycol-based Materials with a Special Focus on Core-Shell Particles for Drug Delivery Application - Shah, Nasrullah; Hussain, Manzoor; Rehan, Touseef; Khan, Abbas; Khan, Zubair U. (Current Pharmaceutical Design, 2022)
Polyethylene glycols (PEG) are water-soluble non-ionic polymeric molecules. PEG and PEG-based materials are used for various important applications, such as solvents, adhesives, adsorbents, drug delivery agents, tissue engineering scaffolds, etc. The coating of nanoparticles with PEG forms core-shell nanoparticles. The PEG-based core-shell nanoparticles are synthesized for the development of high-quality drug delivery systems. In the present review, we first explained the basics and various applications of PEGs and PEG-based composites materials and then concentrated on the PEG-based core-shell nanoparticles for biomedical applications, specifically their use in drug delivery.
Keywords: PEG-based composite materials